دور الرقمنة في تحسين جودة الخدمات الصحية بالمؤسسة العمومية الإستشفائية بن عزة عمر بالطيبات ولاية تقرت - بالضياف، الشيخ; سموحي، عبد الغني (جامعة الوادي University of El Oued, 2024)
تسلط هذه الدراسة الضوء على أهمية الرقمنة في المؤسسات الصحية كخيار استراتيجي تتبناه مختلف الدول، بما في ذلك الجزائر، لمواكبة التطورات العلمية والتكنولوجية المتسارعة في العصر الحديث ، فقد أصبحت التكنولوجيا الرقمية ضرورة ملحة في كافة القطاعات ، وخاصة في القطاع الصحي الذي يمس حياة الإنسان بشكل مباشر حيث تهدف هذه الدراسة إلى تقييم مدى ملاءمة البيئة الرقمية الجزائرية مع الاستراتيجية الوطنية للرقمنة، وتحديد متطلباتها الإلكترونية لتحسين جودة الخدمات الصحية وتعزيز كفاءة المنظومة المعلوماتية ، وخلصت الدراسة إلى مجموعة من المقترحات، أهمها ضرورة تثمين الجهود المبذولة في مجال الرقمنة الصحية وتعزيزها بالإمكانيات اللازمة، مع التركيز على تقليص التكاليف وتحديد النقائص. كما أوصت الدراسة بتفعيل آليات جديدة وخلق أرضية رقمية صحية عصرية ناجعة وفعالة تساهم بشكل كبير في تحسين إدارة المؤسسات الصحية وتحقيق التميز في تقديم الخدمات. This study highlights the significance of digitalization in healthcare institutions as a strategic option adopted by various countries, including Algeria, to keep pace with the rapid scientific and technological developments in the modern era. Digital technology has become an urgent necessity in all sectors, especially in the healthcare sector, which directly affects human life. The study aims to assess the compatibility of the Algerian digital environment with the national digitalization strategy and to identify its electronic requirements to improve the quality of health services and enhance the efficiency of the information system. The study concluded with a set of recommendations, the most important of which is the need to appreciate the efforts made in the field of digital health and to strengthen them with the necessary resources, with a focus on reducing costs and identifying shortcomings. The study also recommended activating new mechanisms and creating an effective and modern digital health platform that significantly contributes to improving the management of healthcare institutions and achieving excellence in service delivery.
ماستر سياسة عامة